TIPOLOGI ARSITEKTUR MELAYU RUMAH LONTIOK DESA KUAPAN, KAMPAR, RIAU - Helen, Nurrul; Laili Dwi Annisa; Dewi, Oriana Paramita; Al Husaini, Muhd. Arief; Mashuri, Mashuri; Saspriatnadi, Morian (RUSTIC, 2024)
Traditional Indonesian architecture showcases a unique local identity and is a treasure in the cultural heritage of Indonesia. One of the distinctive architectural styles in Indonesia is Malay architecture, which exhibits diverse typologies when compared to several other architectural works in the country. This article aims to identify the characteristics and typology of Lontiok houses in Malay architecture to ensure the preservation and conservation of Lontiok Malay houses. The method employed in this research is qualitative, using a case study approach. The findings of this research reveal that the typology of spatial arrangement in Lontiok houses consists of a front porch, bedroom, middle porch, back porch, front stairs, and back stairs. The typology of the structure and construction of Lontiok houses includes a lontiok-shaped roof, a ridge beam with a "drinking elephant" profile oriented parallel to the road, a single eave without ornamentation, 22 pillars, doors comprising front, side, and back doors, windows with 2 leaves, odd stairs consisting of 5 steps, an attic for storage, wooden floors, walls made of tongue and groove wood, and a foundation of umpak stones. Moreover, the Lontiok houses in this research exhibit a variety of decorations with Malay floral motifs found on doors, windows, ventilation openings, foundation pillars, inner walls, and water storage jars.